Strengthening Business Capital in Micro, Small, and Medium Enterprises (MSMEs) through Investment in Peer-to-Peer Lending Platforms - Monica Resavita; Muhamad Mujib (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The purpose of this study is to elaborate on investment schemes within peer-to-peer lending platforms as a means of strengthening capital for Micro, Small, and Medium Enterprises (MSMEs). The research design and procedures employed a qualitative approach using literature review analysis techniques. The results revealed that public interest in investing through peer-to-peer lending platforms can increase the availability of capital for MSMEs, considering that not all MSMEs obtain financing from banks. Therefore, the availability of capital on peer-to-peer lending platforms can serve as an alternative funding option for MSMEs. The higher the public interest in investing on these platforms, the more capital becomes available. Five factors influence public interest in investing in peer-to-peer lending platforms: risk perception, financial literacy, ease of access, and attractive returns